Identification of Characteristic Genomic Markers in Human Hepatoma HuH-7 and Huh7.5.1-8 Cell Lines - Kawamoto, Masaki; Yamaji, Toshiyuki; Saito, Kyoko; Shirasago, Yoshitaka; Satomura, Kazuhiro; Endo, Toshinori; Fukasawa, Masayoshi; Hanada, Kentaro; Osada, Naoki (Frontiers in Genetics, 2020)
The human hepatoma-derived HuH-7 cell line and its derivatives (Huh7.5 and Huh7.5.1) have been widely used as a convenient experimental substitute for primary hepatocytes. In particular, these cell lines represent host cells suitable for propagating the hepatitis C virus (HCV) in vitro. The Huh7.5.1-8 cell line, a subline of Huh7.5.1, can propagate HCV more efficiently than its parental cells. To provide genomic information for cells’ quality control, we performed whole-genome sequencing of HuH-7 and Huh7.5.1-8 and identified their characteristic genomic deletions, some of which are applicable to an in-house test for cell authentication. Among the genes related to HCV infection and replication, 53 genes were found to carry missense or loss-of-function mutations likely specific to the Huh7 and/or Huh7.5.1-8. Eight genes, including DDX58 (RIG-I), BAX, EP300, and SPP1 (osteopontin), contained mutations observed only in Huh7.5.1-8 or mutations with higher frequency in Huh7.5.1-8. These mutations might be relevant to phenotypic differences between the two cell lines and may also serve as genetic markers to distinguish Huh7.5.1-8 cells from the ancestral Huh7 cells.